The Role of the Economy in the Republic of Uzbekistan - Sultonovich, Musinov Dilshod; oʻg‘li, Adashev Shoxrux Botir; qizi, Umurzoqova Sevinch Karim (Journal of Innovation in Education and Social Research, 2024)
In this scientific article, the term "competitive economy" refers to a national economy that grows at a reasonable pace and proportionally, in which the necessary conditions for private entrepreneurship are created, based on the laws of a market economy that serves to constantly improve living standards. An economic system is an open economic system in which production resources move freely and are regulated by a market mechanism.